Mapping the collateral object within ar-rahn contract from its classical rulings to the current issues (BIS Humanities and Social Science, 2026)
Ar-rahn scheme is one of many contracts in Islamic law that helps the people’s financial needs. It came to modify the same scheme that practiced in Jahiliyah era, where the creditor can freely take the collateral object whenever the pledgor unable to pay the debt. However, despite the prophetic practice and the generated rules, there are still legal issues that still arise. One of the issue areas of ar-rahn contract is about the collateral object (marhūn). Thus, this study aimed to draw the map of what classical rulings on ar-rahn and its issues development in modern era. This discussion is a qualitative type of study and it has involved the secondary data. The data analyzed through content analysis approach within the classical Islamic rulings from Four Islamic Mazhabs. Through the practice of Prophet Muhammad (PBUH) and the classical rulings generated by the Fuqaha of Islamic Mazhabs, the issues of ar-rahn contract can be drawn and related it to the current development issues. The study shows that the collateral object issues could be referred back to two areas, both are the collateral type and the collateral ownership. The map has described that there is an agreement between Fuqaha on the Shariah compliance type of collateral. It has to be valuable objects that permitted by Shariah. Through this topic area, it raised the issue of mixed compliance object that need to be divided first before it could be pledged. Second issue is the ownership where Fuqaha also agree to its principle, even though it is not the pledgor’s belonging it needs to be through the owner permission to be pledged. This ownership’s topic area has been breached by current development issues where someone pledge the undivided shared-inheritance without other heirs’ consent. On the other hand, the legal violation is done by Islamic financial institution where it auctioned the pledged-object without the pledgor’s permission.